Facile preparation of carbon microcapsules containing phase-change material with enhanced thermal properties - Tahan Latibari S.; Mehrali M.; Mehrali M.; Mahlia T.M.I.; Metselaar H.S.C. (Hindawi Publishing Corporation, 2023)
This study describes the hydrothermal synthesis of a novel carbon/palmitic acid (PA) microencapsulated phase change material (MEPCM). The field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) images confirm that spherical capsules of uniform size were formed with a mean diameter of 6.42 m. The melting and freezing temperature were found to be slightly lower than those of pure PA with little undercooling. The composite retained 75% of the latent heat of pure PA. Thermal stability of the MEPCM was found to be better than that of pure PA. The thermal conductivity of MEPCM was increased by as much as 41% at 30°C. Due to its good thermal properties and chemical and mechanical stability, the carbon/PA MEPCM displays a good potential for thermal energy storage systems. © 2014 Sara Tahan Latibari et al.